Human Cell-Based in vitro Phenotypic Profiling for Drug Safety-Related Attrition - Berg, Ellen L. (Frontiers in Big Data, 2019)
Ensuring the safety of new drugs is critically important to regulators, pharmaceutical researchers and patients alike. While animal testing continues to be the primary approach for de-risking new drugs, unexpected toxicities still account for some 20-30% of clinical trial failures. Improved methods for safety attrition that incorporate human-relevant biology are needed. This need has spurred interest in non-animal alternatives or new approach methods (NAMs) including in vitro and in silico models that utilize advances in the culture of human cells and thus are more relevant to human clinical outcomes. These methods consist of in vitro phenotypic assays using human primary and induced pluripotent stem cells in various assay formats including advanced cellular systems such as organoids, bio-printed tissues and organs-on-a-chip. Despite the promise of these human-based phenotypic approaches, adoption of these platforms into drug discovery for reducing safety-related attrition has been slow. Here we discuss the importance of incorporating human biology into the de-risking process and the value of large-scale human cell-based phenotypic profiling. We describe learnings from our experience with human primary cell-based assays in developing in vitro-based toxicity signatures. We then propose a strategy for incorporating human-relevant biology into early stages of drug discovery.